2000
DOI: 10.1002/(sici)1097-0223(200005)20:5<378::aid-pd815>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of beta‐thalassaemia in Pakistan: experience in a Muslim country

Abstract: A service for prenatal diagnosis of beta-thalassaemia was introduced in Pakistan in May 1994. Two renowned Islamic scholars, consulted before the service was introduced, ruled that a pregnancy can be terminated if the fetus is affected by a serious genetic disorder, and if termination is before 120 days (17 weeks) of gestation. During the first 3(1/2) years of the service 300 couples requested the test. Almost all the couples had been informed by their treating doctors. Most diagnoses were made between 10 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
0
10
3
Order By: Relevance
“…A number of authors suggest that most Pakistani couples at risk of having a child with β-thalassaemia major are in favour of termination of pregnancy for the condition (Ahmed et al, 2000;Modell et al, 2000a), particularly if prenatal diagnosis and termination of pregnancy are offered in the first trimester of pregnancy (Petrou et al, 1990). So the low reduction in the number of births of children affected with β-thalassaemia major in the United Kingdom may be because prenatal diagnosis is offered late (Modell et al, 1997) or services are being withheld by health professionals owing to their assumptions that Pakistanis would not opt for termination because of their religious beliefs (Atkin and Ahmad, 1998;Anionwu and Atkin, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of authors suggest that most Pakistani couples at risk of having a child with β-thalassaemia major are in favour of termination of pregnancy for the condition (Ahmed et al, 2000;Modell et al, 2000a), particularly if prenatal diagnosis and termination of pregnancy are offered in the first trimester of pregnancy (Petrou et al, 1990). So the low reduction in the number of births of children affected with β-thalassaemia major in the United Kingdom may be because prenatal diagnosis is offered late (Modell et al, 1997) or services are being withheld by health professionals owing to their assumptions that Pakistanis would not opt for termination because of their religious beliefs (Atkin and Ahmad, 1998;Anionwu and Atkin, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…There is no equivalent ruling on termination of pregnancy in the Islamic state of Pakistan, although prior to the introduction of prenatal diagnosis in Pakistan, Ahmed et al (2000) consulted two renowned Pakistani religious scholars, who confirmed that abortion for a confirmed severe disorder is permissible within 120 days of gestation. These different Islamic authorities prohibit termination of pregnancy after 120 days, even if the foetus is affected, although termination is permissible after 120 days if the foetus poses a threat to the life of the pregnant woman.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations